MANAGEMENT MODEL DEVELOPMENT FOR DRIED BANANA COMMUNITY PRODUCT - ไกยวรรณ์, ยุทธ; โสไกร, ประกาศิต; ผลาพรม, กุสุมา; ณ วัฒนะประเสริฐ, กฤษณ์ชาคริตส; ตามถิ่นไทย, พรชัย; มั่งคั่ง, กิตติคุณ (Academic Journal Phranakhon Rajabhat University, 2018)
This research is focuses on participatory action research (PAR) between research group and dried banana community product (DBCP) at Nong Pla Lai sub-district, Tha Din Dam, Chai Badan District, Lopburi Province, by this research aims to (1) raise dried banana community product to the standard of community products (SCP), and (2) develop a dried banana community product management by the knowledge transfer to the community. Methodology used mixed method research between qualitative and quantitative research method in 6 steps as follows, 1) research team meeting 2) the study area with the group of dried banana community product 3) analyze and synthesing knowledge needs 4) develop hand out 5) knowledge transfer and 6) follow up. The research results revealed the following: 1. DBCP group members need 5 topics, 1)packaging development 2 financial 3) logistics management and distribution channels 4) control and quality inspection and 5) step to apply of SCP. 2. Before the DBCP group training buying 400 kg of raw banana per week, 5 baht per kilogram, earning 6,000 baht. After training, the DBCP group produced 1 kilogram of dried bananas for sale at the tourist attraction, price per boxis 145 baht, average sales of 17.50 boxes per week. The group has an average income of 2,537.50 baht per week, so that total income for group is 8,537.50 baht or increased percentage 42.92 baht per week.